Nightly fasting duration is not associated with the prevalence of metabolic syndrome among non‐shift workers: The Furukawa Nutrition and Health Studymx. Issue 1 (27th May 2020) - Ueda, Mariko; Inoue, Yosuke; Hu, Huan; Eguchi, Masafumi; Islam, Zobida; Miki, Takako; Fukunaga, Ami; Kochi, Takeshi; Akter, Shamima; Kabe, Isamu; Akamatsu, Rie; Mizoue, Tetsuya
Abstract: Objectives: While several experimental studies in animals and humans have suggested the protective effect of nightly fasting duration (NFD) against cardiometabolic risk factors, few population‐based studies have been conducted. This study aimed to investigate the association between NFD and metabolic syndrome (MetS) among Japanese non‐shift workers. Methods: A subset of 1054 non‐shift workers from the Furukawa Nutrition and Health Study were included in this analysis. Participants completed dietary and lifestyle surveys during a periodic checkup. NFD was defined as the time between dinner and breakfast and was categorized into four groups (ie, ≥12 hours, 11 hours, 10 hours, and ≤9 hours). MetS was defined as ≥3 of the following components: high waist circumference (≥90 cm [men] and ≥80 cm [women]), high triglycerides (≥150 mg/dL), low high‐density lipoprotein cholesterol (<40 mg/dL [men] and <50 mg/dL [women]), hypertension (systolic blood pressure ≥130 mm Hg or diastolic blood pressure ≥85 mm Hg), and high fasting glucose (fasting plasma glucose ≥100 mg/dL or hemoglobin A1c ≥5.6%). A multivariable logistic regression model was used to examine the association between NFD and MetS. Results: The odds ratios (95% confidence intervals) of MetS for the highest (≥12 hours) through lowest (≤9 hours) NFD categories were 1.00 (reference), 0.83 (0.51‐1.35), 0.83 (0.48‐1.43), and 0.80 (0.43‐1.48) ( P for trend = 0.50) after adjusting for covariates. Further analyses on the relationship between NFD and each MetS component found no significant associations. Conclusions: We did not find any evidence of a significant association between NFD and MetS among non‐shift workers in Japan.